Tumor Glucose and Fatty Acid Metabolism in the Context of Anthracycline and Taxane-Based (Neo)Adjuvant Chemotherapy in Breast Carcinomas - Tőkés, Anna Mária; Vári-Kakas, Stefan; Kulka, Janina; Törőcsik, Beáta (Frontiers in Oncology, 2022)
Breast cancer is characterized by considerable metabolic diversity. A relatively high percent of patients diagnosed with breast carcinoma do not respond to standard-of-care treatment and alteration in metabolic pathways is considered as one of the major mechanisms underlying therapeutic resistance. Consequently there is an emerging need to understand how metabolism shapes therapy response, therapy resistance and not ultimately to analyze the metabolic changes occurring after different treatment regimens. The most commonly applied neoadjuvant chemotherapy regimens in breast cancer contain an anthracycline (doxorubicin or epirubicin) in combination or sequentially administered with taxanes (paclitaxel or docetaxel). Despite several efforts drug resistance is prevalent in many types of breast cancer decreasing patients’ survival. Understanding how tumor cells rapidly rewire their signaling pathways to persist after neoadjuvant cancer treatment have to be analysed in detail and in a more complex system to enable scientists to design novel treatment strategies that target different aspects of tumor cells and tumor resistance. Tumor heterogeneity, the rapidly changing environmental context, differences in nutrients use among different cell types, the cooperative or competitive relationships between cells pose additional challenges in profound analyses of metabolic changes in different breast carcinoma subtypes and by using different treatment protocols. Delineating the contribution of metabolic pathways to tumor differentiation, progression and resistance to different drugs is also in the focus of several research. The present review discusses the changes in glucose and fatty acid pathways associated with the most frequently applied chemotherapeutic drugs in breast cancer, as well the underlying molecular mechanisms and corresponding novel therapeutic strategies